PERLINDUNGAN SOSIAL BAGI ANAK-ANAK FAKIR MISKIN - Strategi Memutus Mata Rantai Kemiskinan - Suradi Suradi (Politeknik Kesejahteraan Sosial, 2009)
Development of social welfare implemented to help every one who have experienced social dysfunction, including children who have abandoned to the poor households. In the year 2009, children stranded in Indonesia is still quite large numbers, its estimated 17.6 million people or 22.90 percent of the population of children. The condition has been associated with menerable because of declining quality of the young generation and the threat to the sustainability of devel- opment in the future. Therefore, the necessary handling really in the form of social protection programs for children are poor and needy. Design Vocational social protection for children re- ferred to the poor integrated with poverty reduction programs.Keyword : children of poverty, social protection, social investment,sustainable development.